How to get others to adopt your recommendation - Duarte, Nancy (MIT Sloan Management Review, 2019)
When a business is growing fast, decisions can get lost in the fray - especially if it's unclear that a decision even needs to be made. People in the workplace bring recommendations to four audiences: a manager or top executive (those who approve a recommendation), and peers or a broader set of stakeholders (those who execute a recommendation). To sell an idea and get others to take action, you have to understand what your particular audience needs to hear.